Early Isometric Eversion and Inversion Changes after Acute Ankle Sprains - Gediminas Tankevičius; Donata Lankaitė; Aleksandras Kriščiūnas; Albertas Skurvydas (Lithuanian Sports University, 2018)
Research background and hypothesis. Most of the methods used to monitor ankle condition after acute ankle sprains do not provide knowledge about the functional state of the ankle, which is mostly dependent on muscles and proprioception. For this purpose we used isometric testing. Research aim: to detect early isometric eversion and inversion peak torque changes after acute ankle sprains, and to compare them to the usual methods. Research methods. The subjects were 80 athletes with acute grade II ankle sprain. All subjects were randomized into  Isometric Testing  Group  (40  subjects),  and  Control  Group  (40  subjects).  Both  groups  underwent  the  same rehabilitation programme. We measured isometric peak torque and peak torque differences between the healthy and injured legs in eversion and inversion movements of the ankle. The outcome measures were pain on activity, swelling, Lower Extremity Functional Scale score, isometric eversion and inversion strength, Square hop test, and Figure of Eight hop test. Research results. There were no significant differences between parameters measured in both groups. Statistical analysis indicated significantly lower eversion and inversion strength of the injured limb, significant eversion and inversion deficit changes during the whole study. Pain on activity, and swelling changes were significant only on the first two weeks. Lower Extremity Functional Scale score changes were significant all three weeks. Eversion and inversion deficit correlated with Lower Extremity Functional Scale score. Conclusion. Isometric testing detects early eversion and inversion changes and helps monitoring rehabilitation after acute lateral ankle sprains. Keywords: peak torque, rehabilitation, monitoring.